Fotojornalismo em cenários de convergência: reconfigurações, inovação, cultura participativa e práticas profissionais - SIQUEIRA, Thaís Christina Coelho (Universidade Federal do Pará, 2018)
This research aims to investigate the reconfigurations through the photojournalism in the context of culture of convergence (SILVA JUNIOR, 2012), characterized by technological, market, social and cultural transformations (JENKINS, 2009). Such changes alter the ways of producing and consuming content, leading many communication companies to invest in innovation and to rethink their practices. In this scenario is photography, which since the beginning of the 20th century accompanies the written text in the constitution of news from newspapers, gain more information autonomy, becoming, in many cases, protagonist of the information. We start from the assumption that in this scenario the photojournalism comes to occupy a central place in the construction of the news. In view of this, this study focuses on three central questions: what changes can be observed in the current photojournalism in terms of innovation in languages and formats? How is the participation of users in photographic production for news portals? And how do these transformations affect the professional practices of photojournalists? For a better understanding of these processes are discussed convergence culture concepts and, more specifically, convergence journalism (SALAVERRÍA; NEGREDO, 2008; SALAVERRÍA, 2010; SALAVERRÍA, AVILÉS E MASIP, 2010); the particulars of cyber media (HERSCOVITZ, 2009; ZAMORA, 2011); reproducibility and multiplication of technical images (BENJAMIN, 2012; 2014); the types of images present in the press (BAEZA, 2001); the characteristics of photojournalism on the web, mainly in its convergent stage (SILVA JUNIOR, 2012); the photojournalistic genres (SOJO, 1997); the formats of photography used by journalism in contemporary times (PEREIRA, 2016); innovation in journalism (FUCK; VILHA, 2011; BARBOSA, 2011; MACHADO, 2010; FONTOURA, 2015; MARTINS, 2017); and participatory culture (JENKINS, 2009; JENKINS; GREEN; FORD, 2014). Besides that, we will also discuss the concepts of narrativity (MOTTA, 2013); of photographic narrative in the culture of convergence (SALLET, 2015; HENN; SALLET, 2012); and the implications of the culture of convergence on the professional practices of photojournalists (SILVA JUNIOR, 2011; 2012; SOUSA, 2013; SALLET, 2014; FERREIRA, 2014; RAMOS E MAROCCO, 2017). We start from direct observation and content analysis to examine the photojournalistic content in the websites Diário Online (DOL), UOL and Clarín, based on the photographic categories prepared byPereira (2016). The methodology also includes semi-open interviews with photojournalists and news websites editors and with a photojournalist and researcher, seeking to discuss the professional experiences and the visions of these subjects about the photojournalistic production in the convergent context. The results of this study point out that the news portals have sought to embrace innovation in photojournalism, investing in multimedia resources that make possible to explore the informative potential of photography, such as galleries, slideshows and 360º images. We also observed a reconfiguration in the narrative forms of photojournalism, with emphasis to the photographic production in sequence, a growing participation of the public in the production of images that compose as analyzed news and increase the space for this participation, with a view to the users' engagement. Finally, we identify that, in general, professionals point these transformations even as a natural process in the development of photojournalism and believe that, with strategies, training and a greater appreciation of their work by companies, professionals tend to expand their repertory.